2004
DOI: 10.1002/ejoc.200300578
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Odor of Aliphatic Musks: Discovery of a New Class of Odorants

Abstract: To find new aliphatic musks, we synthesized the propionates (12), and of hydroxyacetic acid 1-(5Ј,5Ј-dimethylcyclohex-1Ј-enyl)ethyl ester (13) starting from 1-(3Ј,3Ј-dimethylcyclohex-1Ј-enyl)-ethanone (5) and 1-ethynyl-3,3-dimethylcyclohexanol (9). We found that the 3,3-dimethylcyclohexenyl derivatives 8 (odor threshold 0.2 ng/air) and 12 (odor threshold 0.6 ng/air) are superior musk odorants, and, thus, we constructed 1,2,4-trimethylpent-2-enyloxy analogues as seco versions. The synthesis of the esters 17−26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
31
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 12 publications
0
31
0
2
Order By: Relevance
“…We found that the introduction of the CC bond indeed had a major impact on the intensity and character of the compounds. 10 times weaker than 23 [27]. 5 ± 6 times more powerful than Helvetolide (23).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…We found that the introduction of the CC bond indeed had a major impact on the intensity and character of the compounds. 10 times weaker than 23 [27]. 5 ± 6 times more powerful than Helvetolide (23).…”
mentioning
confidence: 94%
“…Starting from artemone ( 1-(3,3-dimethylcyclohex-1-enyl)ethanone) and 1-(5,5dimethylcyclohex-1-enyl)ethanone, available by Rupe rearrangement of ethynylcyclohexanol, we prepared the unsaturated analogs 27, 28, 29, and 30 of Helvetolide (23) and Romandolide (24) [27]. We found that the introduction of the CC bond indeed had a major impact on the intensity and character of the compounds.…”
mentioning
confidence: 99%
“…Unfortunately, when reduced with 0.5 mol-equiv. of LiAlD 4 , ester (À)-16d was prone to a more rapid 1,4-hydride addition, leading to the dideuterated aldehyde (À)-20 16 ) 17 ) in 70% yield [11a] [14] 6 ). This drawback was overcome by oxidizing the monodeuterated allyl alcohol (À)-17a (pyridinium chlorochromate (PCC), CH 2 Cl 2 , yield > 90%) to a ca.…”
mentioning
confidence: 99%
“…As examples of a musk-like perfume ingredient (Scheme 6), we esterified the known intermediate alcohols (þ)-21a [15] and (þ)-21b [16] [17] 6 ) (yield 93%), respectively. In the first case, measurement is made with the major peak at m/z 132/129, and confirmed with the m/z 60/57 fragment.…”
mentioning
confidence: 99%
“…The ethyl malonate 8 was described as the molecule with the strongest musk odor. Last but not least, Kraft and Eichenberger of Givaudan [9] introduced a CC bond in the cyclohexyl moiety of 9, with the side chains unaltered. All synthesized molecules of this type possess musk odors with different connotations.…”
mentioning
confidence: 99%